PENERAPAN METODE RATING SCALE DALAM RANCANG BANGUN SISTEM E-TASK EVALUATION PADA INDUSTRI RETAIL BAHAN BANGUNAN - Muhammad Jonni; Nur Fadilah Fatma; Rachmat Destriana; Lisa Fitriani Ishak (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
The building materials retail industry involves various operational activities that require employees to perform tasks with different levels of complexity. Employee performance evaluation is often conducted manually, which may lead to subjective assessments and difficulties in continuous performance monitoring. Therefore, a system that supports objective and structured task evaluation is required. This study aims to design and develop an E-Task Evaluation system by implementing the Rating Scale method in the building materials retail industry. The Rating Scale method is applied to provide quantitative performance assessments based on predefined indicators. The research stages include system requirement analysis, system design, implementation, and system testing. The results indicate that the developed E-Task Evaluation system is able to support employee performance evaluation in a more objective, efficient, and well-documented manner. In addition, the system facilitates management in monitoring employee performance and supporting managerial decision-making. Thus, the implementation of the Rating Scale method in an E-Task Evaluation system can be considered an effective solution to improve the quality of employee performance evaluation in the building materials retail industry.Â Keywords: E-Task Evaluation, Rating Scale Method, Employee Performance Evaluation, Building Materials Retail Industry, Information System